2013
DOI: 10.2188/jea.je20120161
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Profile of the Japan Collaborative Cohort Study at Final Follow-up

Abstract: The Japan Collaborative Cohort Study for Evaluation of Cancer Risk (JACC Study) was established in the late 1980s to evaluate the risk impact of lifestyle factors and levels of serum components on human health. During the 20-year follow-up period, the results of the study have been published in almost 200 original articles in peer-reviewed English-language journals. However, continued follow-up of the study subjects became difficult because of the retirements of principal researchers, city mergers throughout J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
178
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 137 publications
(180 citation statements)
references
References 2 publications
2
178
0
Order By: Relevance
“…The Japan Collaborative Cohort Study for Evaluation of Cancer Risk (JACC Study) was 4 established in 1988-90 and has been described in detail elsewhere [14]. Briefly, 110,585 5 (46,395 men and 64,190 women) apparently healthy inhabitants aged 40 to 79 years 6 from 45 areas throughout Japan were enrolled.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…The Japan Collaborative Cohort Study for Evaluation of Cancer Risk (JACC Study) was 4 established in 1988-90 and has been described in detail elsewhere [14]. Briefly, 110,585 5 (46,395 men and 64,190 women) apparently healthy inhabitants aged 40 to 79 years 6 from 45 areas throughout Japan were enrolled.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…The JACC Study is a large-scale cohort study, started in 1988-90, which has been described in detail elsewhere [26,27]. Briefly, the cohort consisted of 110,585 individuals, 46,395 men and 64,190 women aged 40-79 years, living in 45 areas across Japan.…”
Section: Study Populationmentioning
confidence: 99%
“…For example, a 1998 meta-analysis of 18 studies found no significant association between H. pylori and risk of coronary heart disease (CHD), a major component of CVD 14) . Furthermore, neither of the two recent cohort studies showed a significant, positive associa-Study, 4287 men and 4043 women died from CVD (18). For our nested case-control study, the cases that were selected met the criteria of having provided a baseline blood sample and having died from CHD and stroke, as determined by the JACC Study, during the follow-up until December 31, 2003 18) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neither of the two recent cohort studies showed a significant, positive associa-Study, 4287 men and 4043 women died from CVD (18). For our nested case-control study, the cases that were selected met the criteria of having provided a baseline blood sample and having died from CHD and stroke, as determined by the JACC Study, during the follow-up until December 31, 2003 18) . Those who were identified in the JACC Study as being diseasefree at the time the study ended were then selected from the remaining participants as controls 18) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation